Nutrien Tercerna Dan Energi Metabolis Puyuh Yang Mendapattepunglimbah Penetasan Dengan Atau Tanpa Kerabang - Indreswari, Rysca; Murtini, Murtini (JURNAL RISET AGRIBISNIS & PETERNAKAN, 2018)
Abstrak This research aimed to investigate the effect of whole hatchery waste meal (WHWM) or shelless hatchery waste meal (SHWM) in the ration on digestible nutrient and apparent metabolizable energy (AME).A total of 500 quails (Coturnix coturnix japonica) 30 days with average initial body weight 94,7 ± 4,2 g were used. The research wasdesigned to completely randomized design with 5 treatments and 5 replicate with 20 quails per replicate. The dietary treatments were: P0 = basal ration, P1 = 96% basal ration + 4% WHWM, P2 = 92% basal ration + 8% WHWM, P3 = 96% basal ration+ 4% SHWM and P4 = 92% basal ration + 8% SHWM. Commercial ration was fed to quails aged 30–39days.At the age of 40–42 days quails were adapted to basal ration. The nutrient digestibility was measured using total collection method after 2 × 28days of treatment. The data were analyzed using variance analysis and if there was a treatment effect, continued by orthogonal contrast test.The results showed that feeding WHWM or SHWM up to 8% increasedthe digestible crude fat and AME but did not increase digestible crude protein and dry matter. The digestible crude fat and AME of quails fed SHWM was higher than that of quails fed WHWM. Furthermore, the digestible crude fat of quails fed 8% WHWM was higher than that of quails 4%, but the opposite result was obtainedforAME. Feeding 8% SHWM generated in a higher digestible crude fat than 4% SHWM. Keywords: hatchery waste meal,digestible nutrient, apparent metabolizable energy, quails